Application of Photo-Realism in Making Gamelan Kenong 3D Objects in Gamelan VR - Stevanus Tetuko Kristianto; Clara Hetty Primasari; Thomas Adi Purnomo Sidhi; Yohanes Priadi Wibisono; Djoko Budiyanto Setyohadi (LPPM UTDI (d.h STMIK AKAKOM) Yogyakarta, 2022)
In creating a simulated world, it is very necessary that the environment, objects, and experiences be similar to the original conditions in the real world. Simulation can be carried out using virtual reality technology, in which environments and objects can be created as desired. The creation of these three-dimensional objects can be achieved by taking into account the 10 principles of photorealism to get realistic objects like those in the real world. In this research, objects from the Kenong gamelan will be created using the principles or characteristics of photorealism. In this study, an assessment of three-dimensional objects was made by distributing questionnaires in which the selected respondents gave a value of 1–5 for each photorealism characteristic of each object. From the results of the assessment carried out, it was found that the 3D objects that were previously made received a value above the average, which means that they meet the characteristics of photorealism. Data was also obtained indicating that realistic 3D objects are required in a simulation in order for the simulation to be felt more strongly or for the user to feel the feeling as closely as possible when playing gamelan. From the results that have been obtained, it is recommended to follow the principle of photorealism when creating 3D objects for simulation needs.